2004
DOI: 10.1086/423418
|View full text |Cite
|
Sign up to set email alerts
|

A High Spatial Resolution Infrared View of the T Tauri Multiple System

Abstract: We present the results of our monitoring study of the IR photometric and spectroscopic variability of the T Tau multiple system. We also present data on the apparent position of T Tau S with respect to T Tau N, and two new spatially resolved observations of the T Tau Sa-Sb binary. T Tau N has not varied by more than 0.2 magnitudes in K and L' flux during the 8 years of our observations, though its Br gamma and Br alpha emission line fluxes have varied by nearly a factor of four during this time. For the unreso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
130
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(151 citation statements)
references
References 69 publications
21
130
0
Order By: Relevance
“…Previous studies found H 2 emission around T Tau N and S (Kasper et al 2002;Beck et al 2004;Gustafsson et al 2010), which our observations also confirm. Our CntK2, Br-γ, and H 2 images (Fig.…”
Section: Classical Imagingsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies found H 2 emission around T Tau N and S (Kasper et al 2002;Beck et al 2004;Gustafsson et al 2010), which our observations also confirm. Our CntK2, Br-γ, and H 2 images (Fig.…”
Section: Classical Imagingsupporting
confidence: 91%
“…This is in marked contrast to the latest K-band brightness ratio measurements, obtained in January 2014, in which Sa was about 0.8 mag fainter than Sb (Schaefer et al 2014). This variability of T Tau Sa of 1.7 mag in less than a year is similar to the photometric behaviour shown prior to 2006 (Beck et al 2004;Duchêne et al 2005), and demonstrates that the period of lesser variability reported from −2013(van Boekel et al 2010Schaefer et al 2014) has come to an end.…”
Section: Classical Imagingsupporting
confidence: 82%
“…This requires one to assume that the IR flux ratio within the T Tau S system remains constant. Evidence for large variability in at least one of the two components of the system is growing, however (Ghez et al 1991;Beck et al 2004).…”
Section: Fitting Methodsmentioning
confidence: 99%
“…All astrometric measurements listed in Beck et al (2004) and Duchêne et al (2005) are included in our fit 1 . Two additional observations of the system were recently published by Mayama et al (2006).…”
Section: Ir Astrometric Datasetmentioning
confidence: 99%
See 1 more Smart Citation